THE USE OF WASTE BAMBOO PIECES AS A PARTIAL SUBSTITUTION OF COARSE AGGREGATES TO INCREASE THE COMPRESSIVE STRENGTH OF CONCRETE - MUHAMMAD ARDIYAN DENYADI; LYDIA DARMIYANTI; INDRIASARI (CV KULTURA DIGITAL MEDIA, 2025)
Utilizing waste as an alternative building material is becoming an effective solution to environmental problems and is popular in developing countries. On the other hand, the concrete industry, a key component of construction, continues to innovate to improve quality and efficiency. The increasing demand for concrete is driving the development of mix designs that meet stringent quality and compressive strength standards, while taking into account environmental sustainability. Advances in concrete technology spur research initiatives to improve its quality and efficiency of use, with innovations in material selection and execution methodologies. This is aimed at meeting the increasing needs and overcoming construction challenges. Modern concrete is required to perform optimally in less time, requiring effective additives for performance enhancement. Recent research has integrated bamboo waste from the handicraft industry as a component of concrete mixes, increasing the speed of project execution and providing a sustainable solution in waste management. The authors were interested in conducting an in-depth study on improving the compressive strength of concrete by integrating waste bamboo pieces. The concrete studied had a f´c strength of 25 MPa (K-300) and was tested at 7, 14, and 28 days to assess the effectiveness of bamboo as an additive. The test results are expected to provide significant data on the viability of bamboo waste as a partial substitution for coarse aggregate. The title of the study, “Use of Waste Bamboo Pieces as Partial Substitution for Coarse Aggregate to Increase the Compressive Strength of Concrete,” reflects the objectives of the study and the utilization of sustainable materials in modern construction. Based on the results of the research that has been carried out and the discussion in the previous chapter with the variation of waste bamboo pieces 0%, 10% and 15%, the following conclusions can be drawn: the results of testing the compressive strength of normal concrete at the age of 28 days reached 452 kN (fʹc 26, 1 MPa = 104%), while variation 1 of 10% rolled bamboo cuttings waste decreased in compressive strength, reaching 305 kN (fʹc 17.60 MPa = 70%), and variation 2 of 15% rolled bamboo cuttings waste decreased, reaching 309 kN (fʹc 17.83 MPa = 71%).